2004
DOI: 10.1158/0008-5472.can-04-1760
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Attenuation of Proteolysis-Inducing Factor Stimulated Protein Degradation in Muscle by β-Hydroxy-β-Methylbutyrate

Abstract: The leucine metabolite ␤-hydroxy-␤-methylbutyrate (HMB) prevents muscle protein degradation in cancer-induced weight loss through attenuation of the ubiquitin-proteasome proteolytic pathway. To investigate the mechanism of this effect, the action of HMB on protein breakdown and intracellular signaling leading to increased proteasome expression by the tumor factor proteolysis-inducing factor (PIF) has been studied in vitro using murine myotubes as a surrogate model of skeletal muscle. A comparison has been made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
87
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 31 publications
0
87
0
5
Order By: Relevance
“…As expected, protein synthesis decreased significantly by 30-50% in the presence of all three catabolic agents; however, HMB treatment effectively abolished these reductions. There is also evidence that HMB can attenuate the increase in proteasome activity generated by proteolysis-inducing factor, a tumor-specific product implicated in the development of cancer cachexia (Smith et al, 2004). Moreover, Kornasio and colleagues (2009) reported that myoblasts incubated with HMB showed increased cell number, MyoD and myogenin expression, and myosin heavy chain content compared to untreated conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, protein synthesis decreased significantly by 30-50% in the presence of all three catabolic agents; however, HMB treatment effectively abolished these reductions. There is also evidence that HMB can attenuate the increase in proteasome activity generated by proteolysis-inducing factor, a tumor-specific product implicated in the development of cancer cachexia (Smith et al, 2004). Moreover, Kornasio and colleagues (2009) reported that myoblasts incubated with HMB showed increased cell number, MyoD and myogenin expression, and myosin heavy chain content compared to untreated conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The significance of the convergence of these signaling pathways on NF-κB in cancerrelated muscle atrophy has been shown experimentally in a number of different ways. Both genetic or pharmacologic inhibition of NF-κB prevents muscle mass loss, improves strength, and increases muscle regeneration [2,9,16,28,31,36,46,48,57,70,75]. These numerous studies implicate NF-κB as having much potential as a therapeutic target in cancer-induced muscle loss.…”
Section: Introductionmentioning
confidence: 99%
“…HMB (β-hydroxy-β-mehtylbutyrate) is a normal constituent of muscle that has been hypothesized to protect muscle from stress-related damage, to build lean body mass (LBM) and to decrease muscle breakdown [15]. Studies from 2004 and 2005 demonstrate the role of HMB in preventing muscle loss in cancer patients [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, Smith et al [16,17] studied how HMB may reduce the inflammatory response by down-regulating the action of proteolysis-inducing factor (PIF), normalize metabolism and help prevent muscle breakdown in cancerrelated weight loss. The action of HMB on protein breakdown and intracellular signaling leading to increased proteasome expression by the tumor factor proteolysis-inducing factor (PIF) was studied in vitro using murine myotubes as a surrogate model of skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation